2014
DOI: 10.1093/eurheartj/ehu226
|View full text |Cite
|
Sign up to set email alerts
|

Rate of telomere shortening and cardiovascular damage: a longitudinal study in the 1946 British Birth Cohort

Abstract: AimCross-sectional studies reported associations between short leucocyte telomere length (LTL) and measures of vascular and cardiac damage. However, the contribution of LTL dynamics to the age-related process of cardiovascular (CV) remodelling remains unknown. In this study, we explored whether the rate of LTL shortening can predict CV phenotypes over 10-year follow-up and the influence of established CV risk factors on this relationship.Methods and resultsAll the participants from the MRC National Survey of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Other studies that have found associative relationships have all been cross sectional in nature (e.g., Buxton et al 2011;Shalev et al 2014). Recent studies of adults report that major life stressors (Puterman et al 2015), evidence of vascular damage (Masi et al 2014), and factors associated with the metabolic syndrome, abdominal obesity and smoking (Huzen et al 2014) are associated with increased telomere attrition. Our study is the first investigation of risk factors for telomere attrition in young children; the only other two longitudinal studies in children focused on older age groups (Shalev et al 2013;Garcon-Calzon et al 2014).…”
Section: Predictors Of Telomere Attrition Ratementioning
confidence: 99%
“…Other studies that have found associative relationships have all been cross sectional in nature (e.g., Buxton et al 2011;Shalev et al 2014). Recent studies of adults report that major life stressors (Puterman et al 2015), evidence of vascular damage (Masi et al 2014), and factors associated with the metabolic syndrome, abdominal obesity and smoking (Huzen et al 2014) are associated with increased telomere attrition. Our study is the first investigation of risk factors for telomere attrition in young children; the only other two longitudinal studies in children focused on older age groups (Shalev et al 2013;Garcon-Calzon et al 2014).…”
Section: Predictors Of Telomere Attrition Ratementioning
confidence: 99%
“…The previous literature shows inconsistent association of LTL with these subclinical CVD measures, with limited data available in large cohorts, particularly for AAC. In cross-sectional analyses, several European cohorts showed no association of longer LTL with IMT when adjusting for conventional CVD risk factors [4143], or found associations in only a subset of participants (for example obese males) [44]. However, in a Native American population from the Strong Heart Family Study shorter baseline LTL predicted incidence and progression of carotid plaque [11].…”
Section: Discussionmentioning
confidence: 99%
“…Rate of telomere length attrition has been correlated with cardiovascular damage in middle-aged adults, even after adjustment for traditional cardiovascular risk factors [43]. In cross-sectional studies, leukocyte telomere length was inversely associated with carotid intima medial thickness, a marker of cardiovascular disease risk and atherosclerotic damage, in obese men [44].…”
Section: Telomere Length and Dynamics In Somatic Diseasesmentioning
confidence: 99%